The Feasibility of Laparoscopic Surgery in Gynecologic Oncology for Obese and Morbidly Obese Patients. Issue 5 (1st June 2018) - Peng, Jessie; Sinasac, Sarah; Pulman, Katherine J.; Zhang, Liying; Murphy, Joan; Feigenberg, Tomer
Abstract : Background: Surgical interventions are the mainstay of treatment for many gynecological cancers. Although minimally invasive surgery offers many potential advantages, performing laparoscopic pelvic surgery in obese patients remains challenging. To overcome this, many centers have shifted their practice to robotic surgery; however, the high costs associated with robotic surgery are concerning and limit its use. Objective: This study aimed to examine the feasibility of performing laparoscopic gynecologic oncology procedures in obese and morbidly obese patients. Materials and Methods: This retrospective study evaluated patients who underwent laparoscopic surgeries by a gynecologic oncologist from January 2012 to June 2016 at a designated gynecologic oncology center. Patients were categorized as nonobese (body mass index [BMI] < 30 kg/m 2 ), obese (BMI 30–39.9 kg/m 2 ), and morbidly obese (BMI ≥ 40 kg/m 2 ). Intra and postoperative complications and outcomes were recorded. Group differences were computed with Kruskal-Wallis nonparametric test (continuous) or Fisher exact test (categorical). Results: Of 497 patients, 288 were nonobese (58%), 162 obese (33%), and 47 morbidly obese (9%). Complex surgical procedures were performed in 57.4% of obese patients and 55.3% of morbidly obese patients. Although morbidly obese and obese patients had longer operative times (mean of 181 and 166 minutes vs 144 minutes, P = 0.014), conversion from laparoscopy to laparotomy occurred in 9.05% of all patients, with no group differences. Low intraoperative (9%–11%) and severe postoperative (2.41%) complication rates were observed overall, with no group differences. There was no statistically significant difference in the rate of emergency room visits 30 days postoperation between the 3 BMI groups ( P = 0.6108). Average length of postoperative stay was statistically significant ( P = 0.0003) but was low overall (1–2 days). Hospital readmission rates were low, with the lowest rate among morbidly obese patients (2.13%). Conclusions: Our data suggest that laparoscopic gynecologic-oncology procedures for obese patients are feasible and safe.